LOAD CALCULATION SYSTEM OF BOEING 737-300 IN INDONESIA AIRASIA USING MICROSOFT ACCESS 2000 - Mamat Kosim; Drs. Sunarto Usna, MMSi (Jurnal Sistem Informasi, 2007)
In the era of globalization where the competition is no longer limited to the size of the region, country and certain zones, the speed and accuracy are important capital in winning the competition. Information technology is the answer to the need for more and more difficult and menduniannya business competition. PT. Airport Sevices DPD is a company which currently manages Airport Ramp Services on side, or side air where PT. Indonesia AirAsia is an airline which apply the concept of LCC (Low Cost Carrier) or low-cost concept, whereby the efficiency of each expenditure made unless the post is directly related to aviation safety. To calculate the load in the Load & Balance Sheet, in Malaysia's Air Asia Bhd. as the holding company is done manually by the Co-Pilot this is done to cut costs to hire a specific ground staff. However, the special at. Indonesia Air Asia Airport Servicesnya handled by PT. Delta Persada Dwitama the work done by a special ground staff, so that the authors regard it necessary to built a computer program in the efficiency and effectiveness using Microsoft Access 2000.